Sexing in Rattans - Choong, Chee Yen; Wickneswari R., (Malaysian Society of Applied Biology, 2016)
In Malaysia, rattans belonging to Calamus species are regarded as the most economically important non-wood resource from forest after timber. However, the genetic resource of rattans in the wild is much depleted due to over exploitation and lose of forest habitat. Therefore, there is a need to establish large scale plantation to produce enough canes for furniture and handicraft industries. Large scale planting requires sufficient planting materials, and the establishment of seed orchards for seed production is important for supplying sufficient planting materials. However, the dioecy in rattan limits its breeding and cultivation. The dioecious Calamus species have distinct male and female plants, and gender is identified only after the first flowering. Early identification of male and female individuals by molecular markers can help to address the limitation of dioecy for large scale planting. In this paper, we address the dioecy and sex ratio in Calamus species. Subsequently, we discuss the functional genomics of Calamus manan and C. palustris in understanding the sex determination and flower development in rattans.